Confidentiality and Ethical Practice in Child and Adolescent Mental Health. Issue 3 (3rd July 2019) - Walker, Steven
ABSTRACT: This paper examines the concept of confidentiality and the quality of the relationship between young people experiencing mental health problems and social workers supporting them. The nature of a therapeutic intervention brings into focus the rigidities and complexities in adhering to agency and professional guidelines on confidentiality. The paper highlights the tensions and ethical dilemmas in making decisions about risk and whether, when, and how to breach confidentiality.